2014
DOI: 10.1159/000365525
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Compensation and Blood Donor Return: Results of a Donor Survey in Southwest Germany

Abstract: Background/Aims: The aim of this study was to compare donor return patterns of non-compensated and compensated German first-time donors to assess the effect of monetary reward on donor return. Methods: We conducted a retrospective analysis of a donor survey of 3,077 non-compensated and 738 compensated German first-time donors. Survey data were pooled and linked with blood donor return rates within the 1st, 2nd, and 3rd year. Logistic regression models were used to estimate differences in the probability of don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…In the CG, the return rate of male donors (58·3%) was slightly higher than the return rate of female donors (50·9%; P = 0·458), which reflects findings of other studies that male FTDs have a higher return rate than female FTDs . As an example, in the study of Kheiri and Alibeigi , 50% of male FTDs and only 30% of female FTDs returned within a 5‐year follow‐up period.…”
Section: Discussionsupporting
confidence: 70%
“…In the CG, the return rate of male donors (58·3%) was slightly higher than the return rate of female donors (50·9%; P = 0·458), which reflects findings of other studies that male FTDs have a higher return rate than female FTDs . As an example, in the study of Kheiri and Alibeigi , 50% of male FTDs and only 30% of female FTDs returned within a 5‐year follow‐up period.…”
Section: Discussionsupporting
confidence: 70%
“…Both the World Health Organization and the European Commission agree that voluntary, nonremunerated donations would be ideal . The evidence pointing toward the conclusion that receiving cash at least does not improve donation behavior (in the long run) is affirmative; however, how noncash items or health screenings influence donor behavior is still under debate . A recent systematic review found that attitudes toward incentives are mixed and depend on age, donor experience, and the donation reward system of the country of residence …”
mentioning
confidence: 99%
“…6,7 The evidence pointing toward the conclusion that receiving cash at least does not improve donation behavior (in the long run) is affirmative; however, how noncash items or health screenings influence donor behavior is still under debate. [8][9][10] A recent systematic review found that attitudes toward incentives are mixed and depend on age, donor experience, and the donation reward system of the country of residence. 11 In contrast to external motivators, willingness to donate may depend more on personal characteristics, on beliefs and motivations, 12 and on cultural and economic context of the country individuals live in.…”
mentioning
confidence: 99%
“…8. See Weidmann et al (2014) for evidence on how monetary incentives may result in different outcomes in the short-term and long-term in the context of monetary compensation for blood donation.…”
mentioning
confidence: 99%